Ethical issues in biomedical publication - Jones, Anne Hudson; McLellan, Faith (Johns Hopkins University Press, 2000)
Annotation "Highly recommended for those intending to undertake clinical trials or similar research, as well as for those presently engaged in this field, as a refresher course in medical ethics."--JAMA"A very thorough discussion of the various legal and administrative solutions ... The book is well-written, has case material and examples enough to make reading vicariously pleasurable."--Bulletin of Medical Ethics